Potencialidades del turismo étnico en el centro poblado comunidad kechwa el Wayku del distrito de Lamas - Chang Alva, Erika Patricia (2005)
The thesis report, named "Potencialidades del Turismo Étnico del Centro Poblado Comunidad Kechwa el Wayku del Distrito de Lamas" , has the purpose to identify, describe and explain the existent potentialities starting from inventory and the evaluation of its tourist resources , as a manner to propuse strategies to improve its development and the population's standard of living. The Minor Downtown Kechua Wayku, is the Kechwa !amistas cradle, descendants of the Quechuan linguistic family that has resisted the passing of time and express its culture and ethnicity through life styles, dances, parties, clothing and another economic and social activities that preserve its local colour that need being revaluate their cultural identity inside a process inter-cultural under way. The ethnic represents a related- studies series with this community likewise its potential as etno tourism that could develop on the basis of the legal and institutional frame existent to distinct level. in order to study this, we have taken as sample the 10% in a universe of 1842 inhabitants in 750 families. The ethnic as potentialities gather three adaptation modes of the community. The habits and ecosystems , the social structures and the•ideology, which is the beliefs systems seen from an anthropological. The Minor Downtown Kechwa Wayku's cultural and ethic expressions have been identified in a chip, where each potentiality was tried to disintegrate analytically The ethnic tourist future of The Minor Downtown Kechwa Wayku , as tourist support are in function of a program's implementation to develop capabilities in the population with a view to try to obtain their own resources and generate their self support.